Profile of the Physical Condition of Football Extracurricular Participants at the Senior High School/Vocational High School Level in Doro District, Pekalongan Regency - Aditia Pria Mihardita; Dwi Tiga Putri (Indonesian Journal for Physical Education and Sport, 2025)
Good performance in a soccer game is strongly supported by the physical condition of the players to be able to perform various movements. Players who have good physical condition can show optimal performance during the match. This study aims to determine the physical condition profile of extracurricular soccer participants at the SMA / SMK level in Doro District, Pekalongan Regency. Physical condition is an important aspect of athlete performance, especially in the sport of soccer which demands speed, strength, agility, endurance, and flexibility. The research method used was descriptive quantitative with a survey approach. The sample in this study were all active soccer extracurricular participants from three schools (SMA Negeri 1 Doro, SMK Ma'arif NU Doro, and SMK Muhammadiyah Doro) total of 42 students, taken using the total sampling technique. The instrument used was the Indonesian Physical Fitness Test (TKJI), including 60-meter sprint, pull-ups, sit-ups, vertical jump, and 1200-meter run. The results of the analysis showed that most participants had physical conditions in the moderate category (73.81%), followed by the less category (23.81%), and good (2.38%). From the conclusion, it is recommended to increase the variety and intensity of physical exercise in extracurricular programs to improve students' physical performance.